Approaching diamond’s theoretical elasticity and strength limits - Anmin Nie (Nature Portfolio, 2019)
While diamond is the strongest natural material, it fails to reach its theoretical elasticity limits and is brittle. Here, the authors show that thin <100>-orientated diamond nanoneedles can reach diamond’s theoretical strength and elasticity limits in tension.